2019
DOI: 10.1016/j.eclinm.2019.08.010
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Medication-Treated Depression and Anxiety Associated with Long-Term Cancer, Cardiovascular Disease, Diabetes and Osteoarthritis in Community-dwelling Women and Men

Abstract: BackgroundLong-term cancer, cardiovascular disease, diabetes and osteoarthritis may increase the risk of mental disorders, but which was more harmful and whether the associations differed between genders is unclear.MethodsWe included 115,094 participants (54.3% women) aged 45–64 years from the 45 and Up Study who were free of depression, anxiety, and Parkinson's disease at baseline (2006–2009). The incidence of depression and anxiety was identified using claim databases during follow-up until December 2016. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 32 publications
1
10
0
1
Order By: Relevance
“…Similar to other surveys [ 3 , 41 ], both KOA and DS are very common among middle-aged and older people, especially among females. However, gender was not identified as a mediator in the relationship between KOA and DS in this research, which is consistent with another longitudinal study [ 30 ]. And we found no mediating effect of age, either.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Similar to other surveys [ 3 , 41 ], both KOA and DS are very common among middle-aged and older people, especially among females. However, gender was not identified as a mediator in the relationship between KOA and DS in this research, which is consistent with another longitudinal study [ 30 ]. And we found no mediating effect of age, either.…”
Section: Discussionsupporting
confidence: 90%
“…Nicola et al reported that the incidence of DS associated with KOA was 26 per 1000 person-years, KOA patients were more likely to develop DS (odds ratio, = 1.43: 95% CI = 1.03 to 1.98) [ 29 ]. Another study analyzing the association of cancer, cardiovascular disease, diabetes, and OA at baseline with incident depression found that among these four conditions OA had the highest risk for incident depression (HR = 1.94: 95% CI = 1.80 to 2.10) [ 30 ]. However, most of the existing research samples have come from high-income countries, whereas our research provides evidence from China.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship of mental disorders with osteoarthritis (28), cardiometabolic disorders (29), cancer (30), dementia (31), and Parkinson's disease (32,33) has been reported in previous studies. Chronic pain, disability, adverse effects on lifestyle as well as the he perceived loss of health, functional capability and independence in patients with these physical chronic diseases may partly explain the increased risk of mental disorders (34)(35)(36)(37)(38)(39).…”
Section: Discussionmentioning
confidence: 71%
“…In many developed countries, including Scotland [ 6 ], Canada [ 7 ], UK [ 8 ], Denmark [ 9 ], Sweden [ 10 ], Australia [ 11 ] and USA [ 12 ], type 2 diabetes-related mortality has declined steadily. People living with type 2 diabetes are at higher risk of chronic diseases, viral hepatitis and even COVID-19 severity [ 13 16 ]. However, large developing economies such as China reported an ongoing and increasing trend of diabetes mellitus, with diabetes mortality increasing from 5.3 deaths/100,000 people in 1990 to 10.9 deaths/100,000 people in 2017 [ 17 ].…”
Section: Introductionmentioning
confidence: 99%